Implementation Of Social Media Marketing Development For Adda Lantai To Increase Brand Awareness - Hasugian, Dedy Saputra; Alvin, Alvin; Kembau, Agung Stevanus (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The researcher took Adda Lantai as the object of research because Adda Lantai in developing its business did not maximize the use of social media marketing. With this problem, the researcher provided a social media marketing solution to increase Brand Awareness in optimizing posts on social media used on Adda Lantai. This study uses a qualitative method with interview and observation techniques. In order to facilitate Adda Lantai to develop its Social Media marketing, the researcher used a previously designed Content Plan in designing the creation of existing content both on Instagram and on Tiktok. The researcher also used Instagram Advertising and Tiktok Advertising tools to increase Brand Awareness in terms of posts. The results of this study indicate that Adda Lantai needs to develop its Social Media Marketing consistently to increase Brand Awareness and also use Instagram Advertising and Tiktok Advertising in order to reach more audiences from Adda Lantai. In conclusion, to increase Brand Awareness, Adda Lantai is advised to focus more on developing Social Media Marketing, especially in terms of its posts so that in the future more audiences will recognize Adda Lantai.